MENCERMATI AKTIVITAS NGAWEN DI JEMBRANA DARI PERSPEKTIF EKOFENIMISME - Ni Made Wiasti (Bumi Lestari Journal of Environment, 2013)
AbstractEncroachment of protected forest known as ngawen in Jembrana is a violation against theforestry laws, potentially harming the forests and infringing the basic idea of feminism. Inthat respect, this paper is going to examine the strategies and implications of the activity inthe perspective of ecofeminism. In perspective of ecofeminism, it is obvious that ngawenactivity is carried out with a strategy reflecting the anthropocentrism and androcentrism.On the one hand, it implicates the increasingly severe destruction of protected forest; whileon the other hand, it implies a less equitable gender relation in the domestic socio-economicaspect of the pengawens’ household.